The Bézout matrix for Hermite interpolants - Aruliah, D.A.; Corless, R.M.; Diaz-Toca, G.M.; Gonzalez-Vega, L.; Shakoori, A. (Linear algebra and its applications, 2015)
The aim of this paper is to introduce the construction of the Bézout matrix of two univariate polynomials given by values in the Hermite interpolation basis, namely the confluent Bézout matrix. Moreover, if such polynomials have exactly one common simple zero, we describe how to compute it from the null space of the confluent Bézout matrix.